Organelle Phylogenomics and Extensive Conflicting Phylogenetic Signals in the Monocot Order Poales - Wu, Hong; Yang, Jun-Bo; Liu, Jing-Xia; Li, De-Zhu; Ma, Peng-Fei (Frontiers in Plant Science, 2022)
The Poales is one of the largest orders of flowering plants with significant economic and ecological values. Reconstructing the phylogeny of the Poales is important for understanding its evolutionary history and forms the basis for biological studies. However, due to sparse taxon sampling and limited molecular data, previous studies have resulted in a variety of contradictory topologies. In particular, there are three nodes surrounded by incongruence: the phylogenetic ambiguity near the root of the Poales tree, the sister family of Poaceae and the delimitation of the xyrid clade. We conducted comprehensive sampling and reconstructed the phylogenetic tree using plastid and mitochondrial genomic data from 91 and 66 taxa, respectively, representing all the 16 families of Poales. Our analyses support the Bromeliaceae and Typhaceae as the earliest diverging group within the Poales while their phylogenetic relationships in polytomy. The clade of Ecdeiocoleaceae and Joinvilleaceae is recovered as sister group of Poaceae. The three families Mayacaceae, Eriocaulaceae and Xyridaceae of the xyrid assembly diverged successively along the backbone of the Poales phylogeny, and thus this assembly is paraphyletic. Surprisingly, we find substantial phylogenetic conflicts within the plastid genomes of the Poales, as well as among plastid, mitochondrial and nuclear data. These conflicts suggest that the Poales could have a complicated evolutionary history such as rapid radiation and polyploidy, particularly allopolyploidy through hybridization. In all, our study presents new perspicacity into the complex phylogenetic relationships and underlying phylogenetic conflicts within the Poales.